Rapid and non-destructive detection method for water status and water distribution of rice seeds with different vigor - Song, Ping; Kim, Ghiseok; Song, Peng; Yang, Tao; Yue, Xia; Gu, Ying (International Journal of Agricultural and Biological Engineering, 2021)
In this study, newly harvested and aged rice seeds were analyzed to determine their aging process, identify the difference between artificially and naturally aged seeds, and to develop a rapid, accurate, and non-destructive detection method for water status and water distribution of rice seed with different vigor. To this end, an artificially accelerated aging test was conducted on the newly harvested rice seeds. Then, low-field nuclear magnetic resonance (LF-NMR) technology was applied to test the new (Shennong No. 9816, 2018), old (Shennong No. 9816, 2017), and artificially aged seeds (Shennong No. 9816, 2018). A standard germination test was conducted for three types of seeds. Finally, the differences of water status and distribution between rice seeds of different vigor were analyzed based on the standard germination test results and wave spectrometry information collected using LF-NMR. The results indicated that new seeds, old seeds, and the artificially accelerated aging rice seeds all exhibited two water phases, and the vigor of rice seeds after the artificial accelerated aging test was lower than that of new seeds. There were significant differences between the frequencies of bound water at the time of the peak and the time at the end of the peak for the three types of seeds. The two times showed an increasing trend for rice seeds with poor vigor, indicating that the ability of the water in the rice seeds having poor vigor to combine with other substances was weakened. There were significant differences between the distributions of free water peak end time for the three types of seeds. All the rice seeds with poor vigor exhibited a decreasing trend at this time, indicating that the freedom of free water inside the rice seed samples with poor vigor was weakened. The total water content of the artificially aged seeds and the aged seeds was higher than that of the new seeds, but the free water content increased from artificially aged seeds to new seeds to aged seeds. This indicates that LF-NMR technology is an effective detection method that can simply compare the differences in seed vitality with respect to water distribution as well as differentiate the seed internal water content of artificially aged and naturally aged seeds. Keywords: low-field nuclear magnetic resonance, rice seed, water status detection, water distribution detection, seed vigor DOI: 10.25165/j.ijabe.20211402.5780 Citation: Song P, Kim G, Song P, yang T, Yue X, Gu Y. Rapid and non-destructive detection method for water status and water distribution of rice seeds with different vigor. Int J Agric & Biol Eng, 2021; 14(2): 231–238.